Fine Selmer groups and isogeny invariance - Sujatha, Ramdorai; Witte, Malte (Geometry, Algebra, Number Theory, and Their Information Technology Applications, 2016)
We investigate fine Selmer groups for elliptic curves and for Galois representations over a number field. More specifically, we discuss a conjecture, which states that the fine Selmer group of an elliptic curve over the cyclotomic extension is a finitely generated Zp-module.